The Influence of School Principal Management Competence on Management Implementation Through Entrepreneurship Teacher Professionalism as a Moderator Variable - Narisin, Narisin; Murwani, F. Danardana; Sumanto, Agus (IJBLE Scientific Publications Community Inc., 2023)
Maintaining the institution's viability requires making human resources more competitive. Therefore, every educational institution in every country is required to improve the quality of education. Principals of schools and human resources must use strategic management to deliver high-quality education. Implementing School-Based Management (SBM) is a very appropriate way to enhance the caliber of education. By using the expertise of entrepreneurial teachers, this study seeks to ascertain how school principal management competency affects SBM. in vocational schools throughout Mojokerto Regency and City. Quantitative research employing a descriptive survey technique was used to process this study. The sample used in this research was vocational school entrepreneurship teachers in Mojokerto Regency and City, totaling 106 respondents. The study's findings indicate that there is a strong correlation between the management competence of school principals on the implementation of school-based management through the professionalism of entrepreneurial teachers